2011
DOI: 10.1124/dmd.111.038505
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism-Based Inactivation of Cytochrome P450 3A4 by Mibefradil through Heme Destruction

Abstract: ABSTRACT:Mibefradil (Posicor) was developed as a calcium channel blocker for the treatment of chronic hypertension. The compound was withdrawn from the market in 1998 because of the potential for rhabdomyolysis, renal failure, or bradycardia when it was coadministered with other drugs. Mibefradil has previously been shown to be a potent reversible (IC 50

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 34 publications
(33 reference statements)
2
35
1
Order By: Relevance
“…The enzyme structure is perturbed because it is incapable of forming a reduced CO-difference spectrum, indicating that the heme thiolate is disrupted. However, CYP3cide does not act by forming a metabolite-intermediate complex like other amines, and it does not act by forming an adduct to the porphyrin (Foti et al, 2011). Efforts to show covalent binding to the protein have been unsuccessful, although studies to detect drug-topolypeptide or drug to heme via LC/MS will continue to be an area of effort in our laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme structure is perturbed because it is incapable of forming a reduced CO-difference spectrum, indicating that the heme thiolate is disrupted. However, CYP3cide does not act by forming a metabolite-intermediate complex like other amines, and it does not act by forming an adduct to the porphyrin (Foti et al, 2011). Efforts to show covalent binding to the protein have been unsuccessful, although studies to detect drug-topolypeptide or drug to heme via LC/MS will continue to be an area of effort in our laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Mibefradil (8) is an inhibitor of T-type Ca 2+ channels, 27 and was briefly marketed for migraine, but was withdrawn because of drug-drug interactions due to its potent inhibition of CYP3A4. 28 In an earlier study 29 it was shown to have no effect on signal-and extracellular Ca 2+ -dependent increases in [Ca 2+ ] stimulated by oxytocin. In our assay both 7 and 8 were active (albeit not very potent; IC 50 s 67 and above 100 µM respectively) against Orai1-mediated Ca 2+ influx (Table 1) but were not selective with respect to inhibition of the Ca V 2.2 channel (data not shown).…”
Section: Biologymentioning
confidence: 99%
“…3, A and B) suggest that these kinetic schemes will result in log-linear PRA plots. However, there are many examples in the literature of curved PRA plots (He et al, 1998;Voorman et al, 1998;Kanamitsu et al, 2000;Yamano et al, 2001;Heydari et al, 2004;Obach et al, 2007;Bui et al, 2008;Foti et al, 2011). Both quasi-irreversible and partial inactivation kinetics result in concave upward plots (Figs.…”
mentioning
confidence: 99%